Measuring anxiety about ageing and ageism: eye-gaze patterns, facial ageing trajectories and implicit associations - Man, Kimberly Min Xi (2025)
This study aims to investigate ageism and anxiety about ageing among young adults via the Brief Implicit Association Test (BIAT) and eye-tracking, where gaze patterns towards faces of different ages and identities are analysed. Thirty-four female undergraduates (Mage = 20.68) completed the self-reported ageism and ageing anxiety scales, BIAT and a passive-view eye-tracking paradigm in which they viewed the age-manipulated faces across three facial identities (the self, familiar “friend” and the unfamiliar “other”). One sample t-tests against the cut-off scores of the respective scales indicates that participants reported significantly more positive attitudes towards older adults and marginally low ageing anxiety, on average, via self-reported measures. However, via the BIAT, on average, participants held ageist attitudes towards older adults. The attitudinal discrepancies between implicit and explicit measures of ageism supports the precedence of implicit attitudes under cognitive load. Regardless of facial identities, participants fixated significantly longer and more frequently at the eye regions compared to other facial regions, especially for old-aged faces. Old-aged faces were rated the least pleasant but most arousing. Facial images of the self were rated the most arousing. Though explorative in nature, findings of gaze patterns are consistent with the crucial roles of eyes and the Expert Hypothesis of facial processing. This sheds light on visual processing when viewing faces of different ages and identities, besides highlighting the attitudinal complexities of young adults towards older individuals. Findings also opens potential avenues for the integration or micro-behaviors and non-verbal communication strategies to supplement existing intergenerational efforts in mitigating ageism.